2008
DOI: 10.1007/s10549-008-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of breast cancer in California

Abstract: This paper estimates the healthcare costs and the value of lost productivity from premature deaths for California women with breast cancer in 2001, with an updated estimate for 2008. Multiple secondary data sources were used to estimate the healthcare cost of breast cancer. Mortality costs were estimated as the product of the number of deaths and the expected value of a woman's future earnings. The total economic cost of breast cancer in California was $1.43 billion in 2001, or $1.91 billion in 2008 dollars. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 7 publications
3
33
0
2
Order By: Relevance
“…This study follows patterns similar to a study by Max et al, 26 although the study was specific to California women with differences in age distribution and study population. Similarly, Bradley et al 27 used the human capital approach to ascertain the value of lost productivity attributable to premature death, although the findings from this study are not comparable because of differences in age groups and time spans.…”
Section: Discussionsupporting
confidence: 70%
“…This study follows patterns similar to a study by Max et al, 26 although the study was specific to California women with differences in age distribution and study population. Similarly, Bradley et al 27 used the human capital approach to ascertain the value of lost productivity attributable to premature death, although the findings from this study are not comparable because of differences in age groups and time spans.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, the economic impact of breast cancer is high [23-25]. The overall cost of managing local breast cancer was not significantly modified by the new organization, estimated at around €3,500.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previously published research [11][12][13] estimated the average costs for women with and without breast cancer, whereas ours focused on the incremental cost impact. By comparing the costs of breast cancer patients with controls, we estimated the incremental costs related to breast cancer, netting out the indirect costs associated with socio-demographic factors and other comorbid conditions, which is more useful from an economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study using the human capital approach projected that the value of lost productivity attributable to death from breast cancer in the US in 2010 will be $10.9 billion [11]. Another study estimated the economic burden of breast cancer in California [12] and showed that the value of lost productivity from premature deaths in 2001 cost the state of California $1.15 billion, whereas the direct health care cost was $279 million.…”
Section: Introductionmentioning
confidence: 99%